Sedimentary DNA is a promising indicator of the abundance of marine benthos: Insights from the burrowing decapod Upogebia major - Kyosuke Kitabatake; Kentaro Izumi; Natsuko Ito-Kondo; Kenji Okoshi (PLoS ONE, 2025)
Upogebia major (De Haan 1841) is a decapod widely distributed in tidal flats in East Asia and Russia and is a dominant species in some regions. Nevertheless, because the inhabiting deep burrows exceeding a depth of 2 m, conducting quantitative surveys is extremely challenging. These challenges are not unique to this species but are also common to infaunal marine benthos. Therefore, this study focuses on environmental DNA (eDNA). eDNA consists of DNA fragments present in water and sediments and serves as an indicator of the presence and abundance of organisms. In particular, sedimentary DNA (sedDNA) is highly concentrated compared with that found in water. When sedDNA is used as an indicator of abundance, it is essential to first comprehensively understand the relationship between abundance and sedDNA concentration. Hence, the number of burrow openings in U. major was considered as abundance, and the relationship between the seasonal variation in abundance and sedDNA concentration was investigated in three tidal flats with different burrow distributions and topographies. During the growth period of this species in stable bottom environments such as bag-shaped lagoons, 105 copies/g sediment of sedDNA was detected in burrow-rich areas, which was significantly higher than in other areas. This indicated a correlation between abundance and concentration. However, it was found that events such as spawning, strong wave action, and changes in activity due to increase in water temperature induced fluctuations in concentration. Therefore, while the sedDNA concentration has the potential to reflect abundance, it is susceptible to biological and physical influences; hence, caution is required regarding the location and timing of surveys. This study sheds light on a fraction of the relationship between U. major abundance and sedDNA concentration, offering initial insights into the applicability of sedDNA analysis for estimating the abundance of various marine benthos.